Serum SAMD9 as a Potential Prognostic Biomarker for Pancreatic Cancer - Xingyu He; Ying Zheng; Xunjie Cao; Jianhao Zhang; Yang Yang; Qing Zhu (Cancers, 2026)
Background: Pancreatic cancer (PC) is one of the most aggressive malignancies and remains a leading cause of cancer-related mortality worldwide. Despite advances in diagnosis and treatment, reliable biomarkers for detection and prognostic assessment remain limited. Sterile alpha motif domain containing 9 (SAMD9) has been implicated in several human malignancies, but its clinical significance in PC has not been fully elucidated. Therefore, this study aimed to investigate the diagnostic and prognostic value of SAMD9 in PC. Methods: SAMD9 expression was analyzed using transcriptomic data from the TCGA, GTEx, and GEO databases. Kaplan–Meier survival analysis, Cox regression, and receiver operating characteristic (ROC) curve analysis were performed to evaluate its prognostic and diagnostic value. Serum SAMD9 levels were measured by ELISA in 89 patients with PC, 55 patients with benign pancreatic diseases, and 47 healthy controls. Results: SAMD9 expression was significantly elevated in PC tissues and was associated with unfavorable survival. Multivariate Cox regression identified SAMD9 as an independent prognostic factor (HR = 1.704, 95% CI: 1.110–2.617, p < 0.05). ROC analysis demonstrated good diagnostic performance across multiple public cohorts, with AUC values ranging from 0.834 to 0.977. Serum SAMD9 levels were significantly higher in patients with PC than in the control groups (p < 0.05). Patients with high SAMD9 expression also had significantly shorter overall survival. Conclusions: SAMD9 is aberrantly expressed in PC and shows potential as a prognostic biomarker.